Retrograde transvenous thoracic duct embolization for lymphatic leakage after retroperitoneal tumor and lymph node resection: a case report and literature review - Go Kinoshita; Koichi Morisaki; Daisuke Okamoto; Takehiko Aoyagi; Shinichiro Yoshino; Kentaro Inoue; Tomoharu Yoshizumi (Surgical Case Reports)
Abstract Background Postoperative lymphatic leakage is a complication of ineffective conservative treatment for retroperitoneal mass. Herein, we report a case of lymphatic leakage that arose after retroperitoneal tumor resection and that was treated with retrograde transvenous thoracic duct embolization. Case presentation A 28-year-old man with persistent abdominal pain was diagnosed with a large retroperitoneal metastatic tumor measuring 10 cm and a subdiaphragmatic lymph node originating from a testicular tumor. After high orchidectomy and neoadjuvant chemotherapy, the subdiaphragmatic lymph node and retroperitoneal tumor were resected together with the abdominal aorta; the latter was reconstructed using a prosthetic graft. Postoperatively, the patient developed chylothorax. No improvement was observed after conservative treatment that included fasting and somatostatin therapy. The leakage site could not be identified using antegrade lymphangiography of the bilateral inguinal lymph nodes, but was detected using retrograde transvenous lymphangiography. The leakage site was successfully embolized. Conclusion This case report describes successful treatment with retrograde transvenous thoracic duct embolization for chylothorax following resection of a retroperitoneal tumor and lymph node. This approach is a less invasive and more effective mode of treatment for chylothorax and should be considered before surgical thoracic duct ligation when the leakage point cannot be identified using the antegrade approach.